Factors associated with interest in scientific research in dental students of six Cuban universities - Corrales-Reyes, Ibraín Enrique; Villegas-Maestre, José Daniel; Valdés-Gamboa, Leonardo; García-Raga, Mónica; Véliz-Concepción, Olga Lidia; Torres-Fernández, Lilian Susana; Tusell-Hormigó, Diana; Vitón-Castillo, Adrián Alejandro; Torrecilla-Venegas, Rolando; Mejia, Christian R. (Frontiers in Education, 2023)
Introduction To determine the factors associated with interest in scientific research in dental students of six Cuban universities. Methods This is a multicenter cross-sectional analytical study. Interest in scientific research was the dependent variable, and it was assessed through a questionnaire proved to be reliable (Cronbach’s α = 0.88). We obtained adjusted prevalence ratios (aPR), 95% confidence intervals (95% CI), and p values through generalized linear models. Results A total of 587 students were part of the research, and 57.9% manifested interest in scientific research. However, when they were asked if they wanted to pursue a research career in the future, only 45.1% responded affirmatively. We found, through multivariate analysis, that there was more interest in scientific research among those who were student assistants (aPR: 2.42; 95% CI: 1.41–4.16; p = 0.001), those who had previous studies (aPR: 1.35; 95% CI: 1.02–1.79; p = 0.034), and those who had received awards in scientific events (aPR: 1.74; 95% CI: 1.26–2.41; p = 0.001). In contrast, there was less interest among those who were at the clinical stage of their career (aPR: 0.66; 95% CI: 0.49–0.89; p = 0.006), adjusted for seven variables. Conclusions There exists interest in scientific research and we found some factors associated with this. This has to be taken into account in order for educational institutions to generate strategies.